Media Framing of Women Victims of Violence Tiara Angelina Saraswati in the Perspective of Feminist Theory - Nur Rovida Femila Sari; Siti Waqi'atul Hasanah; Luluk Ilma Inun; Lilis Muchlisoh (Jurnal Dakwah dan Komunikasi, 2026)
Purpose − Violence is a form of human rights violation resulting from inequality in society. Data from the Ministry of Women's Empowerment and Child Protection (KemenPPPA) recorded 330,097 cases of gender-based violence against women, an increase of approximately 14.17% compared to the previous year. The phenomenon of gender violence encompasses various physical, psychological, sexual, and economic acts experienced by individuals due to gender identity. This study aims to analyze media framing of female victims of violence through a feminist perspective, focusing on news coverage and social media discourse related to the violence against Tiara Angelina Saraswati, which has been widely discussed on TikTok   Method − The research method used was descriptive qualitative research using Robert Entman's framing analysis. Data were obtained through literature review and observation of content and comments on TikTok social media   Findings − The results show that social media framing is still dominated by narratives that position women as oppressed and powerless, and reinforce the stereotype of women as weak. This type of framing indicates  that social media, indirectly, remains a space for the reproduction of patriarchal values.